Discurso e ação: fontes geradoras de poder político e de liberdade - de Paula, Maria Bernadete Gonçalves (Kairós, 2021)
ARENDT, Hannah. A Condição Humana. Trad. Roberto Raposo, Rio de Janeiro: Ed. Forense Universitária, 11ª ed. 2012 (407p).